2016
DOI: 10.1111/acer.13089
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Caffeine Increases Binge Consumption of Ethanol in Adolescent and Adult Mice, But Produces Additive Motor Stimulation Only in Adolescent Animals

Abstract: Background Binge co-consumption of highly caffeinated energy drinks with alcohol (ethanol) has become a common practice among adolescents/young adults and has been associated with an increased incidence of hazardous behaviors. Animal models are critical in advancing our understanding the neurobehavioral consequences of this form of binge drinking. Surprisingly, virtually no work has explored caffeine and ethanol co-consumption or its long-term consequences in adolescent animals. The primary objective of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Researchers argue that caffeine may counteract the depressant effects of alcohol (Arria & O'Brien ; Peacock & Bruno ; Fritz, Companion, & Boehm ; Fritz et al . ). The modulatory and interactive effects of the other energy drink ingredients on alcohol intake and related behavior remain greatly unexplored.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Researchers argue that caffeine may counteract the depressant effects of alcohol (Arria & O'Brien ; Peacock & Bruno ; Fritz, Companion, & Boehm ; Fritz et al . ). The modulatory and interactive effects of the other energy drink ingredients on alcohol intake and related behavior remain greatly unexplored.…”
Section: Discussionmentioning
confidence: 97%
“…Similar locomotor results were recently observed in adolescent mice when they were allowed to voluntarily consume alcohol, caffeine or its combination in a limited‐access binge‐like alcohol drinking paradigm (Fritz et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the risks of drinking alcohol may be higher with consumption of AmED when compared to alcohol alone because the perceived stimulation is enhanced with an energy drink mixer. Given the importance of drug‐induced stimulation, it is notable that findings from several animal studies from different laboratories have reported that locomotor stimulation changes are enhanced for alcohol caffeine combinations when compared to either drug alone (Fritz et al., ; Hilbert et al., ; May et al., ). In one study, it was observed that binge consumption of alcohol by both adolescent and adult mice increased with caffeine, but only the adolescent mice exhibited robust locomotor stimulant responses to alcohol caffeine combinations (Fritz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of drug‐induced stimulation, it is notable that findings from several animal studies from different laboratories have reported that locomotor stimulation changes are enhanced for alcohol caffeine combinations when compared to either drug alone (Fritz et al., ; Hilbert et al., ; May et al., ). In one study, it was observed that binge consumption of alcohol by both adolescent and adult mice increased with caffeine, but only the adolescent mice exhibited robust locomotor stimulant responses to alcohol caffeine combinations (Fritz et al., ). As such, phase of human brain development and drinking history may be only a few of the important factors to examine in the future in an effort to understand when and by how much desire for alcohol is enhanced with energy drink mixers and how stimulation plays a role in these outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation